2021
DOI: 10.3389/frobt.2021.662030
|View full text |Cite
|
Sign up to set email alerts
|

Educational Robotics and Robot Creativity: An Interdisciplinary Dialogue

Abstract: There is a growing literature concerning robotics and creativity. Although some authors claim that robotics in classrooms may be a promising new tool to address the creativity crisis in school, we often face a lack of theoretical development of the concept of creativity and the mechanisms involved. In this article, we will first provide an overview of existing research using educational robotics to foster creativity. We show that in this line of work the exact mechanisms promoted by robotics activities are rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 109 publications
(159 reference statements)
0
10
0
Order By: Relevance
“…Although technology is advancing at a rapid pace, supporting robotic therapy still faces several challenges. The collaboration between psychologists and programmers seems to have given a new impetus to the resulting product (Gubenko et al, 2021 ) with more recent trials reaching greater methodological quality (Robinson et al, 2019 ). Still, there are many obstacles that need to be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Although technology is advancing at a rapid pace, supporting robotic therapy still faces several challenges. The collaboration between psychologists and programmers seems to have given a new impetus to the resulting product (Gubenko et al, 2021 ) with more recent trials reaching greater methodological quality (Robinson et al, 2019 ). Still, there are many obstacles that need to be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…The instructor could evaluate the learners in real time by engineering analysis data, i.e. by fixing start times and enabling quiz scores to be analyzed quickly, while predicted future learning results would adjust adaptive questions [47].…”
Section: -Discussionmentioning
confidence: 99%
“…Barker and Ansorge [44] showed that students' learning achievement improved by using robots in science, while Kazakoff, Sullivan, and Bers [45] found that robots help the learning of how to write operation control programs. Other researchers have suggested that robots are effective at helping the learning of science, engineering, and technology [46,47].…”
Section: -6-contentmentioning
confidence: 99%
“…P adjustment is carried out with the purpose of eliminating and reducing the error through the proportional adjustment link. Set the P parameter to 100, the speed input is 1000, and the actual speed output is stable at about 1000, as shown in Figure 16 , which is basically in line with the expected output [ 18 ].…”
Section: Educational Experimental Protocol Designmentioning
confidence: 94%